Sensory over-responsivity in children of 3-5 years: A descriptive, analytical study - Watkyns, Ann Frances (Division of Occupational Therapy, 2020)
BACKGROUND: Sensory over-responsivity (SOR) is a type of Sensory Modulation Disorder (SMD), where the individual has an over-responsive behavioural reaction to non-harmful or non-threatening sensory stimulation, which is out of proportion to the stimulus. SOR can negatively impact a child’s engagement and performance in their daily life. SOR is frequently diagnosed by occupational therapists, and deep pressure is an important facet of the treatment of SOR by occupational therapists. Prior research (Alberts & Ronca, 2012) indicates that the component of pressure in the vaginal birth process aids the infant’s neurophysiological adaption to extra-uterine life. This component is absent in elective caesarean section births. This study therefore set out to determine whether method of birth could be associated with SOR, as well as investigating demographic and other variables linked to SOR. It was hypothesised that there would be a higher prevalence of SOR in children aged 3-5 years born by elective caesarean section compared to those born by vaginal birth. The study objectives were: • To establish a profile (demographic and variables linked to SOR) of participants (mother-child dyads) by birth method group (CS or vaginal delivery) • To determine the prevalence of SOR by birth method • To establish if there is a statistically significant difference in SOR and birth method • To establish which variables (for example birth weight, jaundice, birth complications) are associated with SOR METHOD: A quantitative, descriptive, analytical study was conducted with a sample of 91 children between the ages of 3 years 0 months and 4 years 11 months. Children across various language, cultural and socio-economic groups were recruited and allocated to two groups based on their method of birth - vaginal delivery and elective caesarean section. Caregivers of each child completed the Short Sensory Profile 2 (SSP2) questionnaire as well as a demographic information questionnaire. The scores for SOR were calculated for each participant, and prevalence of SOR between the two birth method groups was compared. Demographic variables were tested for significance between the two groups. The variables showing a significant difference were further analysed to determine any association with SOR. RESULTS: There were 91 participants, 58 in the VB group and 33 in the CS group. Mothers in the VB group gave birth at a younger age (U = 499.0, p < .001), were of a lower income level (chi-square = 11.49, df = 2, p = .003) and more likely to be single (Fishers exact p (2-tailed) = .037). The children in the VB group were of a greater gestational age (U = 472.5, p = .001), had a shorter time period before the first breastfeed (U = 478.0, p = .006), and had fewer sleeping difficulties (Fishers exact p (2-tailed) = .003). The prevalence of SOR for the total sample was 22%. There was a significant association in SOR prevalence and birth method (Fishers exact p (2-tailed) = .034), with greater prevalence in the VB group (29%) as opposed to the elective CS group (9%). There were statistically significant associations between SOR and maternal age (U = 380.5, p = .004), marital status (Fishers exact p (2-tailed) = .003) and time after birth to the first breastfeed (U = 394.5, p = .049). CONCLUSION: There was a statistically significant difference in SOR between the two birth method groups, with higher prevalence in the VB group. This was thought to be linked to cultural and language challenges associated with the use of the SSP2, and the impact of low socio-economic circumstances on child development and the ability to regulate sensory input. Recommendations include developing and validating a culturally appropriate sensory profile questionnaire, available in the most common official languages to facilitate the accurate assessment of sensory modulation of all children living in South Africa. In addition, there is a need to test the birth method hypothesis in demographically balanced groups.